Innovation for CI surgery and habilitation in the COVID era: the MERF, Tamil Nadu experience - Kasaragod, Sreenivas Kamath; Nair, K. Shilpa; Natarajan, Kiran; Raghunandhan; Kameswaran, Mohan; Rajeswaran, Ranjith (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Cochlear implantation (CI) is a safe and effective procedure for management of severe-profound hearing loss. Complications are uncommon, but when present, should be identified and managed appropriately. The CI and its habilitation services were halted during this time period. Through this article we have tried to showcase how our institute resumed the CI surgeries and managed its complications as well as how we tackled the problems faced in auditory habilitation of CI candidates. Methods: This was a retrospective review of the challenges in cochlear implantation and its complications during the COVID pandemic. A safe management plan was formulated. All patients were thoroughly evaluated and complications were classified as minor or major and were managed medically or surgically, based on its severity. Postoperative auditory habilitation challenges were also tackled with innovative approaches to habilitation. Results: A stringent protocol was followed during the pandemic. Wound infection, biofilm, device failure were the complications encountered. All challenges and complications were dealt with by an experienced CI surgeon appropriately with successful outcomes. Conclusions: During the pandemic, it was essential to deal with all the challenges in CI and its complications taking all necessary precautions. Complications of CI, although not common required prompt and effective management for optimal outcomes.